2017
DOI: 10.1210/en.2017-00152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maternal Obesity on Placental Lipid Metabolism

Abstract: Obese women, on average, give birth to babies with high fat mass. Placental lipid metabolism alters fetal lipid delivery, potentially moderating neonatal adiposity, yet how it is affected by maternal obesity is poorly understood. We hypothesized that fatty acid (FA) accumulation (esterification) is higher and FA β-oxidation (FAO) is lower in placentas from obese, compared with lean women. We assessed acylcarnitine profiles (lipid oxidation intermediates) in mother-baby-placenta triads, in addition to lipid con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
134
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(156 citation statements)
references
References 54 publications
13
134
3
1
Order By: Relevance
“…In humans, maternal HFD decreases levels of carnitine and short‐ and medium‐chain acylcarnitines in the placenta (Calabuig‐Navarro et al . ). We also show that maternal HFD significantly reduces placental carnitine (C0) and its acylcarnitine derivatives (C2, C3, C8 and C10).…”
Section: Discussionmentioning
confidence: 97%
“…In humans, maternal HFD decreases levels of carnitine and short‐ and medium‐chain acylcarnitines in the placenta (Calabuig‐Navarro et al . ). We also show that maternal HFD significantly reduces placental carnitine (C0) and its acylcarnitine derivatives (C2, C3, C8 and C10).…”
Section: Discussionmentioning
confidence: 97%
“…Impairment of lipid metabolism in women with obesity is found by many researchers 1,6,[9][10][11][12][13] . Increasing TC, LDL cholesterol, and TG with a decrease in HDL cholesterol are considered to be risk factors of perinatal complications, in particular placental dysfunction 2,[14][15][16][17][18][19] .…”
Section: Resultsmentioning
confidence: 98%
“…Further, using an in vitro perfusion system to study placental transfer of palmitic acid, researchers previously reported an elevated uptake and esterification of palmitate by human placenta . Indeed, research has shown a significant increase in lipogenesis and reduced fatty acid oxidation due to fewer mitochondria in placentas of woman with obesity as compared with lean women …”
Section: Maternal Obesity and Fetal Programming Of Healthmentioning
confidence: 99%
“…[33][34][35] Offspring of overweight women are at a higher risk of developing obesity and associated complications such as cardiovascular diseases, in part, due to the role of the placenta in transferring nutrients such as FFAs to the developing fetus. [36][37][38] Indeed, evidence suggests that maternal obesity results in transfer of excess FFAs to the developing fetus, which may induce oxidative stress and inflammatory response, and in turn affect the epigenetic status of lipid sensing genes ( Figure 2). [33][34][35]39] This is believed to influence the early programming of the preadipocytes and insulin signaling in fetal tissues such as liver and heart.…”
Section: Maternal Obesity and Nafldmentioning
confidence: 99%
See 1 more Smart Citation